Flora Annie Steel: A Critical Study of an Unconventional Memsahib - Roye, Susmita (University of Alberta Press, 2017)
Flora Annie Steel (1847–1929) was a contemporary of Rudyard Kipling and rivaled his popularity as a writer during her lifetime, but her legacy faded due to gender-biased politics. She spent 22 years in India, mainly in the Punjab. This collection is the first to focus entirely on this “unconventional memsahib” and her contribution to turn-of-the-century Anglo-Indian literature. The eight essays draw attention to Steel’s multifaceted work—ranging from fiction to journalism to letter writing, from housekeeping manuals to philanthropic activities. These essays, by recognized experts on her life and work, will appeal to interdisciplinary scholars and readers in the fields of British India and Women’s Studies. Contributors: Amrita Banerjee, Helen Pike Bauer, Ralph Crane, Gráinne Goodwin, Alan Johnson, Anna Johnston, Danielle Nielsen, LeeAnne M. Richardson, Susmita Roye